2021
DOI: 10.1016/j.dib.2021.106813
|View full text |Cite
|
Sign up to set email alerts
|

Survey data on the impact of COVID-19 on parental engagement across 23 countries

Abstract: This data article describes the dataset of the International COVID-19 Impact on Parental Engagement Study (ICIPES). ICIPES is a collaborative effort of more than 20 institutions to investigate the ways in which, parents and caregivers built capacity engaged with children's learning during the period of social distancing arising from global COVID-19 pandemic. A series of data were collected using an online survey conducted in 23 countries and had a total sample of 4,658 parents/caregivers. The description of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 11 publications
0
17
0
2
Order By: Relevance
“…Educators identified that students who have less access to a laptop or Internet access due to home location are the possibility to attain low academic achievement and unable to keep up with their classmates (Pruet et al, 2016). Osorio-Saea et al (2021) further investigated the effect of COVID-19 on parental engagement across 23 countries. Their home location determines the engagement, acceptance, and confidence of students toward the online learning environment and culture.…”
Section: Discussionmentioning
confidence: 99%
“…Educators identified that students who have less access to a laptop or Internet access due to home location are the possibility to attain low academic achievement and unable to keep up with their classmates (Pruet et al, 2016). Osorio-Saea et al (2021) further investigated the effect of COVID-19 on parental engagement across 23 countries. Their home location determines the engagement, acceptance, and confidence of students toward the online learning environment and culture.…”
Section: Discussionmentioning
confidence: 99%
“…The data from this study stems from the International COVID-19 Impact on Parental Engagement Study (ICIPES) (Osorio-Saez et al, 2020). ICIPES was a joint effort in 23 countries to investigate the ways in which parents and caregivers engaged with their children's learning during the period of social distancing arising from the global COVID-19 pandemic.…”
Section: Datamentioning
confidence: 99%
“…Children were between grade 1 and 13, which represents between 1 and 13 years of schooling, counting from the beginning of Level 1 of the International Standard Classification of Education-ISCED (UNESCO, 2011). The survey was administered by the University of Bath team using the JISC Online Survey Tool (Osorio-Saez et al, 2020). All respondents gave their informed consent and the research collaborators only had access to the data after it had been fully anonymised.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…En Chile, la entidad a cargo de la recolección de datos fue la Facultad de Educación de la Pontificia Universidad Católica de Chile. Durante 3 meses se difundió de manera online un cuestionario que buscaba conocer la forma en que madres, padres y cuidadores construían capacidades para comprometerse con el aprendizaje de sus hijos (Osorio-Saez et al, 2021).…”
Section: Datosunclassified